Impact of body composition and VO2 max on the competitive success in top-level handball players - Ilic, V.; Ranisavljev, I.; Stefanovic, D.; Ivanovic, V,; Mrdakovic, V. (Collegium Antropologicum, 2015)
The purpose of the study was to determine the morphological and functional characteristics of 32 Serbian national U20 handball players (age 20.43±1.16y; training experience 8.12±1.89y) before European championship in Switzerland (2006) and to determinate their impact on competitive performance and outstanding success achieved. The results show that wing players differ from other players in morphological characteristics. Values for body height, weight, BMI, muscle mass and fat mass were significantly lower compared to the other playing positions. Extremely low values of maximal oxygen uptake (VO2 max) were measured in all players (ranged from 2.68 to 4.66 l×min-1). Pivots had the highest VO2 max in absolute values (3.76 l×min-1), and wing players in relative terms (40.83 ml×kg-1×min-1). Handball is characterized by high intensity intermittent play, followed by a number of walking breaks and quick substitutions. This makes possible to retain high playing intensity during whole match, because players can be given rest periods whenever needed. This will result in a high intensity game that does not necessarily require high VO2 max. Competitive success in modern top-level handball might be more reliant on optimal tactical preparation than on the body composition and VO2 max of an individual athlete.